Conceptualising doctoral supervision in Malaysia as small cultures: PhD graduates’ perspectives - Sahar, Rafidah; Abdullah, Nur Nabilah (Global Council for Anthropological Linguistics (GLOCAL), 2020)
Research on doctoral supervision in the field of Intercultural Communication has traditionally been applied to cross-cultural comparison, especially across national systems and cultural boundaries. However, recent years have witnessed that such comparison is being challenged and re-analysed in light of potential risk of over generalisation and stereotyping in its observation. In this research, we consider the relevance of small cultures notion (Holliday, 1994, 1999) as an alternative approach to conceptualise doctoral supervisory practice as a dynamic on-going group process through which its members make sense of, in order to operate purposefully within particular contexts and shared behaviours. Narrative-based qualitative research was designed to generate and analyse the data. The participants were a purposive sample of six recently graduated PhD students at a Malaysian public university. One-on-one narrative interviews were conducted with the students to gather their supervisory narratives. Analyses of the students’ transcripts were completed using a holistic-content approach (Lieblich et al. 2008). Findings reveal a distinct set of behaviours and understanding that constitute the cultures of supervisory practice in the Malaysian university context. Through small cultures notion, this research proposes that cultures of PhD supervision can be best understood through an analysis of shared norms, behaviours and values between students and supervisors during supervisory practice. This research hopes that the move from a focus on large culture (i.e. Malaysianness per se) to a focus on the meaning-making process between students and supervisors from different backgrounds can avoid education practitioners, especially PhD supervisors, from making stereotyping and overgeneralising assumptions.